2021
DOI: 10.1007/s10856-021-06505-x
|View full text |Cite
|
Sign up to set email alerts
|

Facile modification of polycaprolactone nanofibers with egg white protein

Abstract: Synthetic polymers remain to be a major choice for scaffold fabrication due to their structural stability and mechanical strength. However, the lack of functional moieties limits their application for cell-based therapies which necessitate modification and functionalization. Blending synthetic polymers with natural components is a simple and effective way to achieve the desired biological properties for a scaffold. Herein, nanofibrous mats made of polycaprolactone (PCL) and egg white protein (EWP) blend were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…The water uptake of PCL_Fulbright compared to PCL nanofiber structures is due to the hydrophilicity of phage Fulbright and morphological differences between the two samples. The higher water absorption of the PCL_Fulbright membrane observed compared to PCL agrees with previous research [ 42 , 43 ] where it is reported that the presence of protein and porosity might be mainly responsible for the difference between total water uptake values of PCL fiber mats.…”
Section: Discussionsupporting
confidence: 91%
“…The water uptake of PCL_Fulbright compared to PCL nanofiber structures is due to the hydrophilicity of phage Fulbright and morphological differences between the two samples. The higher water absorption of the PCL_Fulbright membrane observed compared to PCL agrees with previous research [ 42 , 43 ] where it is reported that the presence of protein and porosity might be mainly responsible for the difference between total water uptake values of PCL fiber mats.…”
Section: Discussionsupporting
confidence: 91%
“…While the results of cell growing on the PCL/Gel contains 10% EW, are signi cantly better than the scaffold contains 5% EW and this change is more noticeable after 7 days culturing. On the other hand, the results show that increasing the EW from 10 to 15% in PCL/Gel scaffold reduced the cell growth even less than PCL/Gel without EW [42,43].…”
Section: Investigation Of Biocompatibilitymentioning
confidence: 86%
“…Natural materials are mainly utilized effectively to achieve the desired biological properties (biocompatibility and bioactivity) lacking in other synthetic polymers. However, they must be stabilized by cross-linking or other methods in order to yield a stable material that can maintain its integrity [ 70 , 71 ]. In this case, polymer blending can enable the combination of complementary properties of different synthetic and natural polymers or can be used as a one-step surface modification technique to alter the wettability of electrospun mats [ 72 ].…”
Section: Blended and Composite Fibers Towards Bio-sustainabilitymentioning
confidence: 99%